2020
DOI: 10.1186/s12913-019-4728-3
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of pharmacist home visits for individuals at risk of medication-related problems: a systematic review and meta-analysis of randomised controlled trials

Abstract: Background: Medication mismanagement is a major cause of both hospital admission and nursing home placement of frail older adults. Medication reviews by community pharmacists aim to maximise therapeutic benefit but also minimise harm. Pharmacist-led medication reviews have been the focus of several systematic reviews, but none have focussed on the home setting. Review methods: To determine the effectiveness of pharmacist home visits for individuals at risk of medicationrelated problems we undertook a systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 45 publications
0
34
0
Order By: Relevance
“…In summary, previous evidence, combined with our blinded medical assessments at the individual level, supports that pay for performance based on the recording of codes does not have the intended effect to improve the quality of drug treatment. In a similar vein, repeated systematic reviews have failed to demonstrate beneficial effects of medication reviews on patient-relevant outcomes reflecting the net benefitrisk balance of drug treatment, that is, overall mortality and hospitalizations [2,[21][22][23][24][25][26].…”
Section: Findings In Relation To Other Studiesmentioning
confidence: 99%
“…In summary, previous evidence, combined with our blinded medical assessments at the individual level, supports that pay for performance based on the recording of codes does not have the intended effect to improve the quality of drug treatment. In a similar vein, repeated systematic reviews have failed to demonstrate beneficial effects of medication reviews on patient-relevant outcomes reflecting the net benefitrisk balance of drug treatment, that is, overall mortality and hospitalizations [2,[21][22][23][24][25][26].…”
Section: Findings In Relation To Other Studiesmentioning
confidence: 99%
“…Published evidence around domiciliary medication reviews tends to focus on clinical outcomes, such as validated measures for medication appropriateness [8], suggesting this is where the value of these services lies. However, assessment of whether these services definitively have a positive effect on these outcomes varies [9][10][11][12]. There is a gap in the literature around where the value of these DMR services lies.…”
Section: Introductionmentioning
confidence: 99%
“…We did not use quality-of-life measures, as we found that these fail to capture important symptoms, such as pain and emesis, are difficult to administer with people with cognitive impairment [ 6 ], and reviewers indicate that they are infrequently used in this area [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is little evidence that existing interventions to improve the appropriateness of polypharmacy in older people improve outcomes [27]. Pharmacist-led innovations in pharmaceutical care and computerised decision support improve prescribing but not outcomes [27][28][29][30][31][32], and single-problem initiatives may be ineffective [33]. However, nurses' and carers' contributions to medicines optimisation remain unexplored.…”
Section: Introductionmentioning
confidence: 99%